Experimental and genetic evidence for the impact of CD5 and CD6 expression and variation in inflammatory bowel disease - Casadó-Llombart, Sergi; Velasco-de Andrés, María; Català, Cristina; Leyton-Pereira, Alejandra; Gutiérrez-Cózar, Rebeca; Suárez, Belén; Armiger, Noelia; Carreras, Esther; Esteller, Miriam; Ricart, Elena; Ordás, Ingrid; Gisbert, Javier P.; et al. (Frontiers in Immunology, 2022)
Crohn’s disease (CD) and ulcerative colitis (UC) are inflammatory bowel diseases (IBD) resulting from the interaction of multiple environmental, genetic and immunological factors. CD5 and CD6 are paralogs encoding lymphocyte co-receptors involved in fine-tuning intracellular signals delivered upon antigen-specific recognition, microbial pattern recognition and cell adhesion. While CD5 and CD6 expression and variation is known to influence some immune-mediated inflammatory disorders, their role in IBD remains unclear. To this end, Cd5- and Cd6-deficient mice were subjected to dextran sulfate sodium (DSS)-induced colitis, the most widely used experimental animal model of IBD. The two mouse lines showed opposite results regarding body weight loss and disease activity index (DAI) changes following DSS-induced colitis, thus supporting Cd5 and Cd6 expression involvement in the pathophysiology of this experimental IBD model. Furthermore, DNA samples from IBD patients of the ENEIDA registry were used to test association of CD5 (rs2241002 and rs2229177) and CD6 (rs17824933, rs11230563, and rs12360861) single nucleotide polymorphisms with susceptibility and clinical parameters of CD (n=1352) and UC (n=1013). Generalized linear regression analyses showed association of CD5 variation with CD ileal location (rs2241002CC) and requirement of biological therapies (rs2241002C-rs2229177T haplotype), and with poor UC prognosis (rs2241002T-rs2229177T haplotype). Regarding CD6, association was observed with CD ileal location (rs17824933G) and poor prognosis (rs12360861G), and with left-sided or extensive UC, and absence of ankylosing spondylitis in IBD (rs17824933G). The present experimental and genetic evidence support a role for CD5 and CD6 expression and variation in IBD’s clinical manifestations and therapeutic requirements, providing insight into its pathophysiology and broadening the relevance of both immunomodulatory receptors in immune-mediated disorders.